1990
DOI: 10.1042/bj2720187
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of corticosterone on tissue protein synthesis and insulin-sensitivity in rats in vivo

Abstract: The effect of corticosterone treatment on the sensitivity of muscle protein synthesis to insulin infusion was assessed in postabsorptive young rats. To select the optimal time period for corticosterone treatment, protein synthesis was measured by injection of L-[2,6-3H]phenylalanine (1.5 mmol/kg body weight) 1, 4, 12 or 24 h after injection of corticosterone (5 mg/kg body wt.). Muscle protein synthesis was significantly decreased at 4 h and the effect was maximal by 12 h; liver protein synthesis was elevated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 22 publications
2
16
1
1
Order By: Relevance
“…The effect of insulin on glucocorticoidinduced muscle protein wasting has also been studied in young growing rats. The results of the experiment of Southorn et al (1990) agree with ours; they demonstrated that the responsiveness of muscle protein synthesis to insulin was altered when animals were treated with glucocorticoids and that insulin infusion in vivo did not counteract the decrease in muscle protein synthesis generated by corticosterone. In contrast, the study of Tomas et al (1984) showed that, in diabetic rats treated with corticosterone, insulin replacement in vivo produced improved muscle protein synthesis in a dose-related fashion, suggesting that insulin was able to counteract the effect of the steroids.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The effect of insulin on glucocorticoidinduced muscle protein wasting has also been studied in young growing rats. The results of the experiment of Southorn et al (1990) agree with ours; they demonstrated that the responsiveness of muscle protein synthesis to insulin was altered when animals were treated with glucocorticoids and that insulin infusion in vivo did not counteract the decrease in muscle protein synthesis generated by corticosterone. In contrast, the study of Tomas et al (1984) showed that, in diabetic rats treated with corticosterone, insulin replacement in vivo produced improved muscle protein synthesis in a dose-related fashion, suggesting that insulin was able to counteract the effect of the steroids.…”
Section: Discussionsupporting
confidence: 82%
“…Thus their physiological relevance must be considered with caution since the well-known interactive effect of glucocorticoids and insulin on muscle protein turnover was not taken into account. Indeed, it has previously been shown that glucocorticoids alter the action of insulin on both protein synthesis (Odedra & Millward 1982, Southorn et al 1990) and proteolysis (Southorn et al 1990) in muscle from young growing rats. Louard et al (1994) also showed that DEX treatment antagonizes the anti-proteolytic action of insulin on human skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…As physiological insulin levels already maximally stimulate muscle protein synthesis in vivo, the difference in insulin-stimulated protein synthesis that we observed in vitro should also be found in vivo. The results of both Odedra et al (1983) and Southorn et al (1990) agree with this. They demonstrated that the responsiveness of muscle protein synthesis to insulin was altered when rats were treated with steroids and that insulin infusion in vivo did not counteract the decrease in muscle protein synthesis.…”
Section: Figuresupporting
confidence: 81%
“…Indeed, steroids are also known to be potent diabetogenic agents resulting from both hepatic and peripheral resistance to the action of insulin (Amatruda et al 1985). It is well known that the actions of insulin on muscle glucose uptake (Weinstein et al 1995), glycogen synthesis (Leighton et al1987), protein synthesis (Southorn et al 1990 and proteolysis (Louard et al 1994) are altered after glucocorticoid treatment.…”
Section: Introductionmentioning
confidence: 99%
“…That is, under conditions such as chronic stress or food restriction, this steroid, in both ADX and adrenal-intact animals, has potent effects designed to make glucose available ( I , 3,12,154). These actions involve decreased calorie efficiency and increased breakdown of the body's fat and protein stores, resulting in a decline in body weight (1,12,14,158).…”
Section: Nutrient Ingestion and Metabolismmentioning
confidence: 99%